The Influence Of Entrepreneurship Orientation, Market Orientation And Corporate Social Responsibility Towards Takaful Agency's Business Performance In Malaysia - Nazri, MA; Abd Wahab, K; Omar, NA (Euromed Press, 2024)
Indexed by WOS